TINJAUAN ANALISIS KINERJA LAPORAN KEUANGAN PADA PERUSAHAAN FOOD & BEVERAGE YANG TERDAFTAR DI BEI PADA TAHUN 2013-2017 - Dipa Teruna Awaluddin; Hasanudin Hasanudin (JURNAL REKAYASA INFORMASI, 2020)
Food and beverage companies have an important role for human needs, now many people want fast food. The more consumer interest there is to fulfill a need, the greater the competition in this business. The purpose of this study is to measure the financial performance of food and beverage companies in 2013-2017. Financial performance is measured using a liquidity ratio, solvency ratio, profitability ratio and company performance, then see which companies are good and which companies are performing poorly. The population in this study are all food and beverage companies listed on the Stock Exchange. While the method used in this study uses descriptive methods by analyzing financial ratios, doing recapitulation and ranking to determine the best financial performance of the company. The results of this study indicate that the company that has the best financial performance, PT. Ultrajaya Milk Industry and Trading Company Tbk. Keywords : Liquidity Ratio, Solvability Ratio, Profitability Ratio, and Corporate Financial Performance.